Respuesta :

Answer:

No solution.

Step-by-step explanation:

Distribute.

-3(2x + 1) = 2(-3x - 1)

-6x - 3 = -6x - 2

Combine like terms.

-6x - 3 = -6x - 2 add 3 to both sides

-6x = -6x + 1 add 6x to both sides

0 = 1 this is false.

Because we ended up with a false equation, there is no solution to this equation.

Answer:

no solution

Step-by-step explanation:

Perform the indicated multiplication, using the distributive property.

-3(2x+1)=2(-3x-1)  becomes -6x - 3 = -6x - 2

This has no solution because -3 is never equal to -2.